2018
DOI: 10.7763/ijet.2018.v10.1066
|View full text |Cite
|
Sign up to set email alerts
|

Using CFRP NSM Technique with Roots Planted in Concrete to Strength of Prism Beam for Shear

Abstract: This paper presents experimental results of four prismatic concrete reinforced beam and strengthened by NSM (Near surface mounted) FRP (Fiber Reinforced Polymer) reinforced technique, with additional roots planted in the concrete. The strengthening technique causes load capacity of beams to increase from (6%-8%).A decrease in mid-span deflection was also observed from (4%-5%).Using this technique gave increasing in flexural beam resistant under the same conditions and this increasing was also noted in shear be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results also have shown that cylindrical specimens were higher in compressive strength values compared to other specimens. In 2018, the researchers Hassen et al [6]studied the use of carbon fiber reinforced polymer (CFRP) (Near surface mounted (NSM) Technique with Roots Planted in strengthening shear resistance of prism beam. Four prismatic concrete beams (75×75×500 mm) were casted and tested.…”
Section: Introductionmentioning
confidence: 99%
“…The results also have shown that cylindrical specimens were higher in compressive strength values compared to other specimens. In 2018, the researchers Hassen et al [6]studied the use of carbon fiber reinforced polymer (CFRP) (Near surface mounted (NSM) Technique with Roots Planted in strengthening shear resistance of prism beam. Four prismatic concrete beams (75×75×500 mm) were casted and tested.…”
Section: Introductionmentioning
confidence: 99%